Southward shift of winter wheat area intensifies regional water scarcity in the Beijing-Tianjin-Hebei region - Yan, Qi; Xia, Lang; Zhao, Fen; Zha, Yan; Fan, Lingling; Yang, Peng (Frontiers in Sustainable Food Systems, 2025)
Against the backdrop of intensifying climate change and rapid population growth, the conflict between food production and water scarcity has become increasingly severe. Understanding how crop planting patterns evolve over space and time and regulating regional water footprints is critical for achieving sustainable agriculture under water constraints. However, comprehensive assessments of these hydrological impacts have been limited by the lack of long-term, high-resolution spatial distribution data. This study, conducted in the Beijing-Tianjin-Hebei (BTH) region of China, integrates multi-source remote sensing and meteorological data to develop an adaptive threshold-based algorithm for accurate winter wheat extraction. Using this high-precision mapping approach, we analyzed winter wheat planting dynamics from 1990 to 2019 and evaluated its implications for water resource stress. The proposed method achieves high mapping accuracy with an overall accuracy of 93% and Kappa coefficient of 0.89. Our findings reveal three distinct phases in wheat planting area changes, characterized by initial increase, subsequent decrease, and eventual stabilization. The southward shift in spatial distribution, evidenced by a 58-km migration of the planting centroids, led to significant water resource disparities. The unit-area water footprint in southern regions increased 2.6 times more than in northern areas (p < 0.01). Notably, blue water requirement surged by 68.7%, reaching 11.3 billion m3, while available green water declined by 72.0%. The spatial heterogeneity in water resource sensitivity to cropland changes demonstrates that different regions exhibit markedly different vulnerabilities. These findings highlight the urgent need for region-specific water management strategies. We recommend implementing spatially differentiated measures including irrigation quotas and crop rotation systems. Furthermore, developing coordinated water-food optimization plans could significantly enhance agricultural sustainability.